Studies on the use of faecal analyses to estimate the phosphorus intake by grazing sheep - Baker, Cecil McCalaghan (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1980.